Pendidikan Kesehatan Menggunakan Media Pop-Up Book Dapat Meningkatkan Pengetahuan Kesehatan Gigi dan Mulut Pada Anak Usia Sekolah di SD N Demak Ijo 1 - Rahayu, Septina Putri; Badi'ah, Atik; Suryani, Eko; Prayogi, Agus sarwo (Poltekkes Kemenkes Yogyakarta, 2025)
Oral health is important for overall body health, especially in children aged 6-12 years who are prone to caries. This study aims to determine the effect of health education using pop-up book media on oral health knowledge in grade IV students of SD N Demak Ijo 1. Quantitative research with a quasy experiment design involved 56 students and was analyzed using the Wilcoxon and Mann Whitney tests. The results showed a significant increase in knowledge after the intervention (p = 0.000), so it can be concluded that pop-up book media is effective in increasing the oral health knowledge of school-age children.